Waking the giant : how a changing climate triggers earthquakes, tsunamis, and volcanoes - McGuire, Bill, 1954- (Oxford [England] ; New York : Oxford University Press, 2012)
"The ground beneath our feet may seem safe and solid, but earthquakes, volcanic blasts and other hazardous natural phenomena leave us in no doubt that this isn't the case. The Earth is a dynamic planet of shifting tectonic plates that is responsive to change, particularly when there is a dramatic climate transition. We know that at the end of the last Ice Age, as the great glaciers disappeared, the release in pressure allowed the crust beneath to bounce back. At the same time, staggering volumes of melt water poured into the ocean basins, warping and bending the crust around their margins. The resulting tossing and turning provoked a huge resurgence in volcanic activity, seismic shocks, and monstrous landslides -- the last both above the waves and below. The frightening truth is that temperature rises expected this century are in line with those at the end of the Ice Age. All the signs, warns geophysical hazard specialist Bill McGuire, are that unmitigated climate change due to human activities could bring about a comparable response. Using evidence accumulated from studies of the recent history of our planet, and gleaned from current observations and modeling, he argues convincingly that we ignore at our peril the threats that presented by climate change and the waking giant beneath our feet."--Cover.
The storm after the calm -- Once and future climate -- Nice day for an eruption -- Bouncing back -- Earth in motion -- Water, water, everywhere -- Reawakening the giant.
Includes bibliographical references (p. 271-282) and index.
Keywords: CLIMATIC CHANGES; EARTHQUAKES; TSUNAMIS; VOLCANIC ERUPTIONS